Multisystem inflammatory syndrome in adults after acute coronavirus disease 2019 in a Japanese woman: A case report. Issue 1 (January 2022) - Miyamoto, Kyohei; Koizumi, Yusuke; Tamura, Shinobu; Nakashima, Tsuyoshi; Kobai, Kaori; Tanaka, Rikako; Shibata, Mami; Shima, Nozomu; Nemoto, Shigeki; Fukumoto, Nobu; Kato, Seiya
Abstract: Multisystem inflammatory syndrome in adults (MIS-A) is a rare and emerging syndrome after coronavirus disease 2019 (COVID-19). To the best of our knowledge, Japanese cases of MIS-A are rarely reported. Here, we describe a case of MIS-A in a 44-year-old Japanese woman presenting with multiorgan dysfunction (i.e., cardiovascular and mucocutaneous involvement) and markedly elevated inflammatory markers 2 weeks after recovery from COVID-19. Treatment with intravenous immunoglobulins and corticosteroids resolved her symptoms. On the 13th day, she was discharged from the hospital with no recurrences on follow-up. This study highlights the importance of recognizing this emerging syndrome when treating patients with multiorgan dysfunction after COVID-19.